Association of Neospora caninum and abortions in water buffaloes in Venezuela - Rosaura Pérez-Gil (Revista Científica)
Buffaloes are an important natural host of Neospora caninum; this protozoan causes abortions in bovines. In addition, transplacental transmission is considered the main route of transmission. This research aimed to study the seroprevalence of N. caninum of 223 Bubalus bubalis females; the herd comes from 10 farms in 4 states of Venezuela; in addition, the association between the presence of antibodies against N. caninum with parity and the history of abortions was analyzed. The data was extracted from the SG Software Ganadero version 23, exported to Excel version 2306, and analyzed with IBM SPSS Statistics 20. Antibodies were determined by ELISA using a commercial kit (IDEXX® ). The cut-off value to define positive cases was the coefficient sample/positive ≥ 0.500. A chi-square test was performed to estimate the association between the presence of antibodies against N. caninum with parity and abortions. Of the 223 animals analyzed, 59.2% of the samples were positive for N. caninum antibodies. The percentages of seropositive animals were: 4.0%, 66.4%, 13.0%, 9.0%, 1.8%, 0.4%, 1,3%, and 4% for animals with 0 to 7 calving, respectively. The percentages of positives to N. caninum for buffaloes of parity 1 and 2 were 54.05% and 62.06%, respectively (X2 = 0.630, p=0.427), while the percentage of positives to N. caninum in buffaloes without abortion and with one previous abortion were 54.17% and 74.51%, respectively (X2 = 6.68, p=0.01). In addition, buffaloes with a history of abortion had more odds of being seropositive to N. caninum than those without abortions (2.478, 95%CI:1.2874-4.8834, p = 0.0087). Therefore, it is concluded that N. caninum serology and parity are independent, while N. caninum serology and the occurrence of abortions are associated. These results demonstrate that N. caninum is a risk factor for the occurrence of abortions in water buffaloes, so it is suggested to include this pathology in preventive health programs in herds.